2022
DOI: 10.1016/j.radi.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Amide proton transfer-weighted MRI in the clinical setting – correlation with dynamic susceptibility contrast perfusion in the post-treatment imaging of adult glioma patients at 3T

Abstract: Introduction: We investigated the correlation between amide proton transfer-weighted magnetic resonance imaging (APTw MRI) and dynamic susceptibility contrast (DSC) perfusion in order to assess the potential of APTw MRI as an alternative to DSC in adult brain tumor (glioma) imaging. Methods: After Ethical Committee approval, forty adult patients, treated for histopathologically confirmed glioma (World Health Organization (WHO) grade II-IV), were prospectively imaged at 3 Tesla (3 T) with DSC perfusion and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…PCa tissues exhibit abundant internal neovascularization and heightened blood perfusion. SSmax values and ∆R 2 *peak values serve as common parameters in PWI, effectively portraying tissue characteristics [26][27][28]. In this study, we observed lower SSmax values and ∆R 2 *peak values in PCa lesions, which highlights the potential of these parameters in providing insights into the nature of prostate lesions.…”
Section: Discussionsupporting
confidence: 50%
“…PCa tissues exhibit abundant internal neovascularization and heightened blood perfusion. SSmax values and ∆R 2 *peak values serve as common parameters in PWI, effectively portraying tissue characteristics [26][27][28]. In this study, we observed lower SSmax values and ∆R 2 *peak values in PCa lesions, which highlights the potential of these parameters in providing insights into the nature of prostate lesions.…”
Section: Discussionsupporting
confidence: 50%
“…40 adult patients, treated for histopathologically confirmed glioma (WHO grades II-IV). [33] APTw MRI mean values might be helpful in the differential diagnosis of HGGs and meningiomas or HGGs and LGGs.…”
Section: Mrimentioning
confidence: 99%
“…The relationship between APTw MRI and DSC perfusion was investigated by Friismose and colleagues [33] who evaluated whether APTw MRI could be used as an alternative to magnetic resonance DSC in the imaging of HGG in adult patients (Figure 3G-M) (Table 1). APTw MRI (max) values correlated positively with rCBV (max) in patients treated for cerebral glioma.…”
Section: Major Finding Experimental Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, APT imaging has substantial benefit in that it uses an off-resonance radiofrequency (RF) pulse to detect endogenous mobile proteins and peptides within recurrent gliomas without ionizing radiation. Another clinical advantage of APT imaging is that it is non-invasive with no need for exogenous contrast and is a reproducible technique, which can be a potential alternative to DSC perfusion, especially in patients where contrast agent is contraindicated ( 12 ).…”
Section: Introductionmentioning
confidence: 99%